Pengaruh Current Ratio Dan Return On Asset, Terhadap Quick Ratio Pada Perusahaan Tekstil Dan Garmen Yang Terdaftar Di Bursa Efek Indonesia - Anggita Putri Anugrahtianty (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aims to analyze the effect of the Current Ratio and Return on Assets (ROA) on the Quick Ratio in textile and garment companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The analysis method used is multiple linear regression with secondary data obtained from the companies' financial statements. The results show that the Current Ratio has a significant positive effect on the Quick Ratio, while ROA also has a significant positive effect on the Quick Ratio. This study provides important implications for company management in managing liquidity to improve financial performance.